Penetration of 38% hydrogen peroxide into the pulp chamber in bovine and human teeth submitted to office bleach technique - Afonso Camargo, Samira Esteves; Valera, Marcia Carneiro; Ribeiro Camargo, Carlos Henrique; Gasparoto Mancini, Maria Nadir; Menezes, Marcia Maciel (Elsevier B.V., 2007)
This study evaluated the pulp chamber penetration of peroxide bleaching agent in human and bovine teeth after office bleach technique. All the teeth were sectioned 3 mm apical of the cement-enamel junction and were divided into 2 groups, A (70 third human molars) and B (70 bovine lateral incisors), that were subdivided into A1 and B1 restored by using composite resin, A2 and B2 by using glass ionomer cement, and A3 and B3 by using resin-modified glass ionomer cement; A4, A5, B4, and B5 were not restored. Acetate buffer was placed in the pulp chamber, and the bleaching agent was applied for 40 minutes as follows: A1-A4 and B1-B4, 38% hydrogen peroxide exposure and A5 and B5, immersion into distilled water. The buffer solution was transferred to a glass tube in which leuco crystal violet and horseradish peroxidase were added, producing a blue solution. The optical density of the blue solution was determined by spectrophotometer and converted into microgram equivalents of hydrogen peroxide. Data were submitted to analysis of variance and Dunnett, Kruskal-Wallis, and Tukey tests (5%). A higher level of hydrogen peroxide penetrated into the pulp chamber in resin-modified glass ionomer cements in bovine (0.79 +/- 0.61 mu g) and human (2.27 +/- 0.41 mu g) groups. The bleaching agent penetration into the pulp chamber was higher in human teeth for any experimental situation. The penetration of the hydrogen peroxide depends on restorative materials, and under the conditions of this study human teeth are more susceptible to penetration of bleaching agent into the pulp chamber than bovine teeth.
Keywords: bovine; dental pulp; human; hydrogen peroxide; tooth bleaching